Art imitates the Digital - Nash, Adam (Lumina, 2017)
Where is art in the digital era? This essay identifies the digital as an abstract, formal system. Since art has always relied on formal, abstract systems to carry and deliver itself, what are the implications for art in the digital era? Is the digital a site for art, or is it the other way around? Can there be digital art? Identifying limit and boundary problems as the crucial existential problems for the digital, the essay shows that art has always concerned itself with such problems. This prompts the question as to whether it is possible that human existence and art become the same thing in the digital. Because the digital is currently primarily manipulated in the service of globalist economics, this is clearly not (yet) the case, so what does this mean for art? The essay then briefly examines the self-declared movements of dada, post-digital and post-internet art, concluding that these movements are not capable of questioning the digital as digital, before going on to examine some artists whose practice may be providing guiding lights toward a genuinely digital art.